IMPLEMENTING DUOLINGO ENGLISH TEST TO PREPARE STUDENTS FOR THE INTERNATIONAL MOBILITY PROGRAM AND INDEPENDENT LEARNING INDEPENDENT CAMPUS (MBKM) - Resdiana, Widia; Yulientinah, Dewi Selviani (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2024)
This research aims to determine the students’ perceptions at an international university in Bandung, Indonesia, regarding the DET or Duolingo English Test, which is often used as a requirement for continuing studies and applying for scholarships, and also for internship or international student exchange requirements or often referred to as mobility program called IISMA or Indonesian International Student Mobility Awards, which is an implementation of Independent Learning Independent Campus (MBKM). Then, a DET English proficiency test was held for Year 1 vocational students at the beginning of the semester of the Academic Year 2023/2024 to see the baseline scores, and compare the average scores from the two study programs at the Faculty of Vocational Studies, which are the Diploma 3 and Diploma 4 Study Programs. The score results were analyzed by calculating the average results of the independent sample t-Test, which aims to test whether there is a significant difference in English language skills between the two study programs. The study results showed that 96.5% of respondents had never used Duolingo for an English test, even though 50.9% already knew about Duolingo. Of all the respondents, only one person had a Duolingo score, which is 90. Then, the average score for the D3 Study Program was 68, and D4 was 55, with the highest score from D3 being 105 and from D4 being 95, and the lowest from D3 being 35 and the lowest D4 is 15. Referring to Duolingo's score requirements for the D4 level, which is 100, the study program is still unable to send its candidates for IISMA Program. At the D3 level, the minimum Duolingo score requirement is 90, so this study program can send its candidates for this Program. And the results of the independent sample t test calculations also show that the two study programs have significant differences in English language skills based on the DET.